О биологии размножения пшеничной кошенили Porphyrophora tritici Bod. (Homoptera, Coccinea, Margarodidae) - Л. П. Мкртчян (ՀՀ ԳԱԱ հրատ.)
Исследованы половые органы самок и самцов пшеничной кошенили (Porphyrophora tritici Bod.). Проведено сравнение ее с араратской кошенилью (P. hamelii Brandt). Определен тип строения яичников и выявлены определенные особенности. Ուսումնասիրվել են ցորենի որդան կարմիրի (Porphyrophora tritici Bod.) սեռական օրգանները: Համեմատական աշխատանք է կատարվել դրա և արարատյան որդան կարմիրի միջև (P. hamelii Brandt):The genital organs of male and female Porphyrophora tritici Bod. have been investigated and compared with P. hamelii Brandt. The structure type of ovaries has been stated and certain peculiarities have been found out.
Keywords: Biology; Ecology